1987
DOI: 10.1227/00006123-198710000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Plasmacytoma of the Calvarium: Two Cases Treated by Operation Alone

Abstract: Two cases of solitary plasmacytoma of the calvarium operated on with radical removal are reported. The two patients were not submitted to postoperative radiotherapy, unlike other cases reported in the literature. The authors stress that solitary plasmacytoma of the calvarium may have a good prognosis if radically removed, and in these cases radiotherapy is not necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Our patient underwent surgery with complete resection of tumor (Figure 2). Nevertheless, Arienta et al reported that if total resection has been achieved then radiotherapy should be reserved for case of tumor recurrence [1]. Furthermore, there are reports of complete cure after radiotherapy, because plasma cell neoplasms are exquisitely radiosensitive [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient underwent surgery with complete resection of tumor (Figure 2). Nevertheless, Arienta et al reported that if total resection has been achieved then radiotherapy should be reserved for case of tumor recurrence [1]. Furthermore, there are reports of complete cure after radiotherapy, because plasma cell neoplasms are exquisitely radiosensitive [14].…”
Section: Discussionmentioning
confidence: 99%
“…Craniocerebral localization is rare and constitutes only 0.7 per 100 of all solitary plasmacytomas. They fall into two groups [1]. Those arising from the cranial bones (plasmacytoma of the skull, osseous form) and those arising from the dura mater (dural plasmacytoma, non-osseous form).…”
Section: Introductionmentioning
confidence: 99%
“…1,8) However, intracranial plasmacytoma is very radiosensitive so complete surgical resection and adjuvant radiation therapy is sometimes curative. 2,12,14,25) Therefore, the radiotherapy is given in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports suggest that definitive treatment should consist of complete surgical resection with adjuvant radiation therapy. 1,16) Based on this suggestion, our Case 2 received postoperative radiotherapy after total resection of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Solitary plasmacytoma is a circumscribed neoplastic lesion with no clinical or radiological signs of systemic involvement and accounts for some 7 % of myelomas [1,6,8,21]. Solitary bone plasmacytoma is described as a single lytic lesion without signs of myeloma cells on bone marrow examination, even when paraproteins are present in serum and/or urine.…”
Section: Introductionmentioning
confidence: 99%